Path of the prophets : the ethics-driven life - Schwartz, Barry L. (University of Nebraska Press, 2018)
"Devoted to the legacy of the biblical prophets, identifies the prophetic moment in the lives of 18 biblical characters, offers up an intimate view of their inner thoughts, illuminates their ethical legacies, and challenges each of us to walk the path of the prophets today"--